Political violence in South Asia - Zaman, Fahmida; Nāsarīna, Jobāidā 1976-; Riaz, Ali 1958- (Abingdon, Oxon Routledge, Taylor and Francis Group, 2019)
"Political violence has remained an integral part of South Asian society for decades. The region has witnessed and continued to encounter violence for achieving political objectives from above and from below. Violence is perpetrated by the state, by non-state actors, and used by the citizens as a form of resistance. Ethnic insurgency, religion-inspired extremism, and ideology-driven hostility are examples of violent acts that have emerged as challenges to the states which have responded with violence in the form of civil war and through violations of human rights disregarding international norms. This book explores various dimensions of political violence in South Asia, namely in Bangladesh, India, Nepal, Pakistan, and Sri Lanka. Each chapter either speaks to an important aspect of the political violence or provides an overall picture of the nature and scope of political violence in the respective country. Political violence is understood in the larger sense of political, that is, above and beyond institutions, and also as an integral part of social relationships where social norms and the role of individual agency play seminal roles. The contributions in this book incorporate both institutional and non-institutional dimensions of political violence. Exploring how everyday life in South Asian states and societies is transformed by the engagement with violence through direct and indirect methods, this book adopts an interdisciplinary framework; diverse methods are employed - from ethnographic readings to more macro level analyses. The phenomenon is explored from historical, sociological, and political perspectives. This book will be useful as a supplementary text in courses on South Asian Studies in general and South Asian politics in particular."--Provided by publisher.
Introduction: perspectives on political violence in South Asia / Ali Riaz, Fahmida Zaman, and Zobaida Nasreen -- A taxonomy of political violence in South Asia / Ali Riaz -- Towards a relational view of political violence / David Jackman -- Representation of political violence in South Asian English fiction / Fahmida Zaman -- Explaining political violence in contemporary Bangladesh (2001-2017) / Saimum Parvez -- State violence and the everyday: the ecology of suspicion and distrust / Zobaida Nasreen -- Communal violence in India: strategies for prevention / Maya Chadda -- The politics of Muzaffarnagar violence in 2013, Utar Pradesh, India / Mujibur Rehman -- State violence and youth resistance perspectives from Indian-held Kashmir / Hafsa Kanjwal -- Maoism and political violence of the People's War in Nepal / Subho Basu
Strategic logic of political violence in Pakistan / Farhat Haq -- Island of violence: Sinhalese Buddhist majoritarianism and ethno-religious conflict in Sri Lanka / Neil Devotta -- Political violence and post-colonial state building in Sri Lanka / Nirmal Ranjith Dewasiri.
Includes bibliographical references and index.
Keywords: Political violence -- South Asia; South Asia -- Politics and government -- 21st century